1997
DOI: 10.1002/art.1780400514
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine production in muscle tissue of patients with idiopathic inflammatory myopathies

Abstract: Objective. To study cytokine expression in muscle tissues of patients with inflammatory myopathies and to compare the profiles of patients with polymyositis (PM), inclusion body myositis (IBM), and dermatomyositis (DM). Methods. We performed indirect immunohistochemistry studies of muscle tissue sections with a panel of 16 different cytokine‐specific monoclonal antibodies, directed against interleukin‐1α, (IL‐1α), IL‐1β, IL‐1 receptor antagonist (IL‐1ra), IL‐2, IL‐3, IL‐4, IL‐6, IL‐8, IL‐10, IL‐13, interferon‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
177
2
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 247 publications
(191 citation statements)
references
References 21 publications
4
177
2
8
Order By: Relevance
“…34,35 IL-1␣ is mainly expressed by endothelial cells of capillaries, arterioles, and venules in inflammatory myopathies 36 and IL-1␣ has also been observed in muscle tissue without any infiltration of inflammatory cells. 4 Thus one possibility is that MHC class II and class I expression is regulated in response to IL-1␣.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 IL-1␣ is mainly expressed by endothelial cells of capillaries, arterioles, and venules in inflammatory myopathies 36 and IL-1␣ has also been observed in muscle tissue without any infiltration of inflammatory cells. 4 Thus one possibility is that MHC class II and class I expression is regulated in response to IL-1␣.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis of local muscle tissue hypoxia is supported by increased expression of interleukin-1␣ (IL-1␣), IL-1␤, transforming growth factor ␤, intercellular adhesion molecule 1, and vascular cellular adhesion molecule 1 in the muscle tissue of patients with myositis (10)(11)(12)(13)(14), because these molecules are known to be up-regulated by hypoxia (10)(11)(12)(13). Moreover, the endothelial cells are frequently thickened, resembling endothelial cells of high endothelium venules (HEV), indicating their activation (3,10,11,(15)(16)(17). Notably, such phenotypically changed endothelial cells were observed in patient muscle tissue irrespective of inflammation (15).…”
Section: Polymyositis (Pm) and Dermatomyositis (Dm)mentioning
confidence: 99%
“…Moreover, the endothelial cells are frequently thickened, resembling endothelial cells of high endothelium venules (HEV), indicating their activation (3,10,11,(15)(16)(17). Notably, such phenotypically changed endothelial cells were observed in patient muscle tissue irrespective of inflammation (15). Potentially, such phenotypically changed microvessels might affect the local muscular circulation and hence contribute to tissue hypoxia and metabolic alterations.…”
Section: Polymyositis (Pm) and Dermatomyositis (Dm)mentioning
confidence: 99%
“…An early immunocytochemistry study that evaluated expression of inflammatory mediators in myositis, found predominant presence of IL‐1 α (in endothelial cells), IL‐1 β and TGF‐ β (both in inflammatory cells), albeit no apparent difference in the expression pattern was observed between DM, PM and IBM 147. Similarly, De Bleeker and colleagues detected TNF‐ α in macrophages, endothelial cells, and central myonuclei in IBM, DM, and PM muscle but not in that of nonmyositic controls 148.…”
Section: Pathomechanisms In Ibmmentioning
confidence: 99%